The Relevance of Gender-Based in RA Kartini's Perspective on the Goals of Islamic Education - Putri, Yulita (Advances in Humanities and Contemporary Studies, 2023)
Education is an endless process that becomes the main key to improving the quality of human life. Because a quality human being is not one who only develops on the cognitive side, but also needs the formation of religion and good character. So it's no wonder that various figures in this country are competing to formulate thoughts on education, one of which is Raden Ajeng Kartini who is known as a fighter for emancipation. And the purpose of this study is to describe the relevance of gender-based education in RA Kartini's perspective on the goals of Islamic education. The method used is descriptive qualitative with a literature study approach, then the data is collected, the content is analyzed, and finally concluded according to the theme. The results of the study show that the Relevance of Gender-Based Education in the Perspective of R.A. Kartini's views on Islamic Education Goals include equality education, education without discrimination, and character education where these three things are also manifested in the Qur'an QS AlHujurot verse 13 as the formula for the goals of Islamic education.